The last kids on Earth : the graphic novel - Brallier, Max; Peterson, Scott, 1968- (Viking, 2024)
After the monster apocalypse happened, 13-year-old Jack Sullivan builds a team so he can slay Blarg, an eerily intelligent monster, in a graphic novel version of the New York Times best-selling series.